2020
DOI: 10.1097/shk.0000000000001634
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index and Postpartum Hemorrhage in Vaginal Deliveries: A Multicenter Retrospective Study

Abstract: Introduction: Shock index (SI), calculated by dividing heart rate by systolic blood pressure, is used to detect hemodynamic instability and hypovolemia. In obstetric practice, limited evidence is available regarding its usefulness in detecting postpartum hemorrhage (PPH). We aimed to evaluate the usefulness of SI in detecting PPH in vaginal deliveries using clinical data from 12 primary maternity care units in Japan. Material and methods: In this multicenter retrospective study, a total of 30,820 women who del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 22 publications
2
49
1
2
Order By: Relevance
“…A previous study [22,23] showed that SI positively correlated with the volume of blood product transfusion and level of brinogen. Takafumi Ushida et al reported the cutoff points of SI for PPH (≥1,000 ml) was 0.86 (sensitivity, 53.9%; speci city, 76.0%) [13]. These observations suggested that SI correlated with the need for transfusion with high speci city and negative predictive value which could be used in excluding blood transfusion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study [22,23] showed that SI positively correlated with the volume of blood product transfusion and level of brinogen. Takafumi Ushida et al reported the cutoff points of SI for PPH (≥1,000 ml) was 0.86 (sensitivity, 53.9%; speci city, 76.0%) [13]. These observations suggested that SI correlated with the need for transfusion with high speci city and negative predictive value which could be used in excluding blood transfusion.…”
Section: Discussionmentioning
confidence: 97%
“…Laceration suture or hematoma removal should be performed when laceration of the cervix or vagina occurred. Postoperative adjuvant mifepristone or MTX was required when placental accreta occurred [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Although unlikely, women could possibly receive a RBC transfusion between their baseline Hb test and randomisation, which is not recorded in the trial. While heart rate and blood pressure can be accurately measured, shock index is an imperfect physiological marker of postpartum blood loss with low sensitivity for PPH [ 27 ]. Maternal cardiovascular compensatory mechanisms like haemoconcentration and increased cardiac output after childbirth may obscure early physiologic signs of postpartum bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Shock index is an imperfect physiological marker of postpartum blood loss with low sensitivity for PPH. (27) Maternal cardiovascular compensatory mechanisms like haemoconcentration and increased cardiac output after childbirth may obscure early physiologic signs of postpartum bleeding. Shock can be caused by other conditions like sepsis, although this affected < 1% of trial participants.…”
Section: Discussionmentioning
confidence: 99%